2003
DOI: 10.1590/s0100-84042003000100007
|View full text |Cite
|
Sign up to set email alerts
|

Comparação da morfologia foliar de espécies arbóreas de três estádios sucessionais distintos de floresta ombrófila densa (Floresta Atlântica) no Sul do Brasil

Abstract: -(Comparison of leaf morphology of tree species from three distinct successional stages of tropical rain forest (Atlantic Forest) in Southern Brazil). We investigated the leaf morphology of trees from three distinct successional stages (early, intermediate, late) of a lowland rain forest located near the coast of Paraná State, Brazil. This forest grows on sandy soil with low nutrient content. Leaves from trees from the early successional stage present a higher degree of sclerophylly, having thicker leaves, sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
28

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 31 publications
(42 reference statements)
5
32
0
28
Order By: Relevance
“…According to Boeger et al (1997), all species with xeromorphic characteristics are heliophytes occuring at early stages of succession, and have wide geographic distributions (Reitz et al, 1987). This suggested that the xeromorphic features observed were strategies for survival under adverse environmental conditions, as observed at the early stages of the successional process in sand oligotrophic soils (Boeger et al, 2003). The morphological parameters of leaves from the most studied species were similar to those of species from other lowland rain forests (Grubb et al, 1975;Pyykko, 1979;Roth, 1984;Bongers and Popma, 1990).…”
Section: Resultsmentioning
confidence: 56%
“…According to Boeger et al (1997), all species with xeromorphic characteristics are heliophytes occuring at early stages of succession, and have wide geographic distributions (Reitz et al, 1987). This suggested that the xeromorphic features observed were strategies for survival under adverse environmental conditions, as observed at the early stages of the successional process in sand oligotrophic soils (Boeger et al, 2003). The morphological parameters of leaves from the most studied species were similar to those of species from other lowland rain forests (Grubb et al, 1975;Pyykko, 1979;Roth, 1984;Bongers and Popma, 1990).…”
Section: Resultsmentioning
confidence: 56%
“…Pioneer species commonly present a higher Mg content in green leaves than nonpioneer species (Boeger et al, 2005) because they have higher photosynthetic activity due to the increased exposure to solar radiation, which increases Mg requirement, an essential element for photosynthesis (Larcher, 2000). Moreover, species in the early stages of succession usually present larger amounts of tissue with secondary walls in the leaves, where Mg accumulates, than do plants that feature the more advanced stages of succession (Boeger & Wisniewski, 2003). P. decussata was the only pioneer species that did not fit this pattern.…”
Section: Resultsmentioning
confidence: 98%
“…Agronomy Maringá, v. 38, n. 1, p. 93-101, Jan.-Mar., 2016 certain species to low-fertility soils (Magalhães & Blum, 1999). Pioneer species colonize infertile soils likely through the combination of two characteristics, low nutrient requirements and the efficient use of these elements (Boeger & Wisniewski, 2003), by increasing internal retranslocation, which is influenced by the continuous growth of these plants (Fife & Nambiar, 1997). Thus, pioneer species with fast growth may have higher nutrient retranslocation rates than the non-pioneer species in low-fertility soils.…”
Section: Introductionmentioning
confidence: 99%
“…Kieffer, 1913 (Diptera, Chironomidae) and Phylloicus bromeliarum Müller, 1880 (Trichoptera, Calamoceratidae) was higher when exposed to leaf detritus enriched with nutrients (N and P) and suggested that leaf quality is also important to the development of shredders in bromeliad tanks. Possibly, the xeromorphic characteristics of leaf detritus produced in restinga, such as thick cuticles, wax deposition and high tannin content (Rôças et al, 1997;Boeger and Wisniewski, 2003;Mantuano et al, 2006), are related to the absence of typical shredders in the bromeliads studied. However, even with refractory characteristics, leaf detritus may contribute indirectly to maintenance of phytotelmata in the study area because they can provide nutrients to the host plants (Benzing and Renfrow, 1974;Inselsbacher et al, 2007).…”
Section: Discussionmentioning
confidence: 99%